Actuality of Heidegger in seven stages. Sketches for a political project - Calles Rittner, Daniel (Revista de Filosofía, 2021)
The current essay intends to express the actuality of Heidegger’s thinking from a simple and concise hermeneutical interpretation (of context and intentionality) of the German philosopher regarding the concepts of being, Dasein, Sorgeand historicity. This is also a summon for an ethical reinterpretation of Heidegger’s political project in the midst of postmodernity.